2017
DOI: 10.1515/johr-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Silica Fertilizer as an Anti-Herbivore Defense in Cucumber

Abstract: This study aims to improve our understanding of silicon's role in deterring herbivores from Cucumis sativa. We hypothesized that silicon's role in plant defense is due to the presence of silica augmenting other physical and/or chemical defenses used by the plant. Using C. sativa plants treated with either a silica fertilizer treatment (Si+) or a control solution (Si-), we monitored feeding preferences of two types of herbivores, a chewing herbivore (Diabrotica balteata) and a piercing/sucking herbivore (Bemisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…), or mites [5]. Silica containing leaves are stiffer and therefore less attractive to animals [49]. Cotterill et al [50] and Hunt et al [51] showed that Si-fertilized grasses were less eagerly fed on by wild rabbits and locusts than non-fertilized ones.…”
Section: Discussionmentioning
confidence: 99%
“…), or mites [5]. Silica containing leaves are stiffer and therefore less attractive to animals [49]. Cotterill et al [50] and Hunt et al [51] showed that Si-fertilized grasses were less eagerly fed on by wild rabbits and locusts than non-fertilized ones.…”
Section: Discussionmentioning
confidence: 99%
“…Silicified tissues can also wear down insect mouthparts marginally (Kvedaras et al ., 2009) or substantially (Massey & Hartley, 2009) and preclude nutrient absorption in their guts which, in turn, retards their growth (Massey & Hartley, 2009; Frew et al ., 2018). Previous studies have reported the impacts of Si on insects' growth and consumption rates based on both in situ feeding assays on plants (Massey et al ., 2006; Ryalls et al ., 2017; Moise et al ., 2019) and ex situ assays with excised leaves (Moraes et al ., 2004; Callis‐Duehl et al ., 2017; Hall et al ., 2020). Given the inducibility of Si under herbivory, ex situ assays might undermine the actual effects of Si‐based defences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Si application can increase the degree of resistance of host plants to insect pests. In this direction, the effect of Si application for resistance, against the whitefly ( Bemisia tabaci ) has been evaluated in tomato and cucumber [19,56,57]. Si application diminished the whitefly population on cucumber plants by reducing the insect oviposition, increasing growth cycle, and by causing high mortality at the nymph stages [19].…”
Section: Biotic Stressmentioning
confidence: 99%
“…Whereas in soybean, Si application did not affect insect oviposition preferences but caused significant mortality at the nymph stages [56]. Recently, Callis-Duehl et al [57] studied the role of Si application against D. balteata and B. tabaci of cucumber. Plant protection against insect pests with Si application is further correlated with the amount of increment of biochemical compounds like indols [58].…”
Section: Biotic Stressmentioning
confidence: 99%